Dilemma of Taklid and Ijtihad in the Contemporary Era of Hadith Perspective: Comparation of the Thinking of Ahmad Hassan and Nawawi al-Bantani - Jamila Mulidiya Zalza Bila; Layli Nurul Islamiyah; Muhid Muhid; Hitna Bis Sa’adah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study examines the problematic between taqlid and ijtihad in the contemporary era through the perspective of hadith, with a comparative approach to the thoughts of Ahmad Hassan and Shaykh Nawawi al-Bantani. In the midst of developments marked by scientific progress, widespread access to information, and increasing religious awareness, Muslims are faced with the choice between following the opinions of scholars absolutely (taqlid) or trying to understand religion independently through ijtihad. Ahmad Hassan, as a modernist reformist figure, emphasized the importance of returning to the Qur'an and hadith and rejected blind taqlid. Meanwhile, Shaykh Nawawi al-Bantani, a traditionalist scholar, viewed taqlid as a relevant path for the lay community to maintain scientific authority and the continuity of tradition. This study uses a qualitative method with a library study approach and analysis of relevant hadith. The results of the study show that these differences in views are rooted in different social contexts and methodological approaches, but both have the same goal, namely maintaining the integrity of Islamic teachings amidst the dynamics of the times, and this problem needs to be addressed by respecting the opinions of scholars, while still trying to understand Islamic teachings directly from the Qur'an and hadith with critical thinking.